2013
DOI: 10.1120/jacmp.v14i2.4082
|View full text |Cite
|
Sign up to set email alerts
|

Source strength assay of iodine‐125 seeds sealed within sterile packaging

Abstract: Early‐stage prostate cancer is widely treated by iodine‐125 (I‐125) seed implantation. While quality assurance methods are in place to assure consistency in I‐125 seed source strength, current methods involve the breaking of the sterilization package, raising issues concerning sterility and time limitations. The purpose of this study was to develop a method of characterizing the total source strength of I‐125 seeds within a cartridge that has been sealed within a sterilization package and to evaluate the proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…A five‐seed assay worked much better yielding uncertainties around 5% similar to our results. A more recent study7 showed that with proper design and holders, a 15‐seed assay could be performed under sterile conditions and with a 3% uncertainty. The seeds were supplied in a sterile cartridge placed inside a sterile bag for measurement in the well chamber.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A five‐seed assay worked much better yielding uncertainties around 5% similar to our results. A more recent study7 showed that with proper design and holders, a 15‐seed assay could be performed under sterile conditions and with a 3% uncertainty. The seeds were supplied in a sterile cartridge placed inside a sterile bag for measurement in the well chamber.…”
Section: Discussionmentioning
confidence: 99%
“…One is to order extra seeds from the same lot as those to be used in the implant and then assay them 5. Another way is to assay the seeds in sterile packaging using a calibrated well chamber7 or an imaging plate 8. Both solutions have limitations.…”
Section: Introductionmentioning
confidence: 99%
“…A five‐seed assay worked much better yielding uncertainties around 5% similar to our results. A more recent study showed that with proper design and holders, a 15‐seed assay could be performed under sterile conditions and with a 3% uncertainty. The seeds were supplied in a sterile cartridge placed inside a sterile bag for measurement in the well chamber.…”
Section: Discussionmentioning
confidence: 99%
“…One is to order extra seeds from the same lot as those to be used in the implant and then assay them . Another way is to assay the seeds in sterile packaging using a calibrated well chamber or an imaging plate . Both solutions have limitations.…”
Section: Introductionmentioning
confidence: 99%